2020
DOI: 10.1093/neuros/nyaa356
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Effect of Inhalational Anesthetics on Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: BACKGROUND Delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (SAH) has been identified as an independent predictor of poor outcome in numerous studies. OBJECTIVE To investigate the potential protective role of inhalational anesthetics against angiographic vasospasm, DCI, and neurologic outcome in SAH patients. METHODS After Institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…The key findings in our study are as follows: (1) both sevoflurane and desflurane conditioning provided strong protection against large artery vasospasm and microvessel thrombosis after SAH; and (2) sevoflurane and desflurane conditioning improved short-term neurological outcomes after SAH. These findings are important for three key reasons: (1) they provide additional evidence to the growing body of experimental literature indicating inhalational anesthetics as a conditioning agent class provide robust neurovascular protection in SAH; [12][13][14][15][16] (2) they show that the much more commonly used inhalational anesthetics, sevoflurane and desflurane, provide potent and multifaceted protection against DCI in SAH, very similar to that previously reported with isoflurane conditioning; [12][13][14][15][16] and (3) they provide preclinical support for the recently reported protective effect of sevoflurane and desflurane against angiographic vasospasm and DCI in SAH patients [30][31][32]. Given the pharmacologic advantages of sevoflurane and desflurane over isoflurane (e.g., the blood-gas and the oil-gas partition coefficient of isoflurane is significantly larger than that of sevoflurane and desflurane [25,26]-both of which lead to prolonged clinical emergence [19][20][21] from general anesthesia that can confound postprocedure neurological assessment), the very high usage rate of sevoflurane and desflurane in neurosurgical patients, and the proven safety track record of desflurane and sevoflurane in a wide variety of patients, the results from our study have relevant and meaningful implications for the care of SAH patients that deserve further investigation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The key findings in our study are as follows: (1) both sevoflurane and desflurane conditioning provided strong protection against large artery vasospasm and microvessel thrombosis after SAH; and (2) sevoflurane and desflurane conditioning improved short-term neurological outcomes after SAH. These findings are important for three key reasons: (1) they provide additional evidence to the growing body of experimental literature indicating inhalational anesthetics as a conditioning agent class provide robust neurovascular protection in SAH; [12][13][14][15][16] (2) they show that the much more commonly used inhalational anesthetics, sevoflurane and desflurane, provide potent and multifaceted protection against DCI in SAH, very similar to that previously reported with isoflurane conditioning; [12][13][14][15][16] and (3) they provide preclinical support for the recently reported protective effect of sevoflurane and desflurane against angiographic vasospasm and DCI in SAH patients [30][31][32]. Given the pharmacologic advantages of sevoflurane and desflurane over isoflurane (e.g., the blood-gas and the oil-gas partition coefficient of isoflurane is significantly larger than that of sevoflurane and desflurane [25,26]-both of which lead to prolonged clinical emergence [19][20][21] from general anesthesia that can confound postprocedure neurological assessment), the very high usage rate of sevoflurane and desflurane in neurosurgical patients, and the proven safety track record of desflurane and sevoflurane in a wide variety of patients, the results from our study have relevant and meaningful implications for the care of SAH patients that deserve further investigation.…”
Section: Discussionsupporting
confidence: 73%
“…Several clinical studies, including our own, have suggested that desflurane exposure during aneurysm repair in SAH patients is associated with reduced incidence of angiographic vasospasm and DCI [30,31,36]. However, to date, no published preclinical studies have prospectively investigated this relationship.…”
Section: Desflurane Conditioning In Sahmentioning
confidence: 96%
“…With respect to SAH-induced brain injury, SIRT1 has been linked to two of the most important forms of post-ictal secondary brain injury: EBI [34][35][36] and DCI [22]. In the case of anesthetic conditioning, there is a growing body of preclinical and clinical evidence indicating a strong protective effect of inhalational anesthetics against SAH-induced DCI [15,[37][38][39][40]. Milner et al [14] previously noted that isoflurane conditioning provides robust protection against multiple elements of DCI including improved neurologic outcomes in a mouse model of SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous preclinical and clinical studies have shown that inhalational anesthetics were associated with reduced incidence of angiographic vasospasm and DCI. 13 Molecular mechanisms by which inhalational anesthetics provide this DCI protection include upregulation of hypoxia-inducible factor1-α7 and increased expression of endothelial nitric oxide synthase. 14 Similar protective effect with intravenous anesthetics is not known.…”
Section: Inhalational Versus Intravenous Anesthesia and Delayed Cereb...mentioning
confidence: 99%